Assessment of literacy development from cultural-historical perspective - Jabłoński, Sławomir (My University, 2015)
Current research on literacy reduces reading and writing to two separate cognitive processes. In the opinion of Vygotsky, along with progress in using script children develop new higher mental function called written speech. In the opinion of Vygotsky, the development of written speech starts not simultaneously with the beginning of reading and writing instruction but much earlier when children collect their first experiences with a script. It seems to be more complete view on literacy than presented in most research because it including not only cognitive but also emotional processes and communicative context. This approach is illustrated in the study of 944 children aged from 3 to 8 years examined with the use of Literacy Assessment Battery designed with respect of Vygotsky’s theory. Results showed that the battery is a promising tool of literacy assessment especially during kindergarten ages.
Keywords: School readiness; Executive functions; Inhibitory control; Literacy development; Written speech